Cytoplasmic Expression of Human Telomerase Catalytic Protein (hTERT) in Neutrophils: An Immunoelectron Microscopy Study - Lepreux, Sébastien; Doudnikoff, Evelyne; Aubert, Incarnation; Bioulac-Sage, Paulette; Bloch, Bertrand; Martin-Negrier, Marie-Laure (Ultrastructural pathology, 2008)
Human telomerase comprises a catalytic protein subunit (hTERT) and an RNA subunit (hTR). Telomerase extends chromosome ends in compensation for the attrition of the telomeres during replication. In this work, the authors explore the expression of hTERT and hTR in neutrophils, respectively by immunochemistry techniques and in situ hybridization. hTERT was strongly expressed in neutrophils cytoplasm. The ultrastructural study showed that the gold particles were not associated with specific organelles but scattered in the cytosol. hTR was not expressed. hTERT is expressed in the cytoplasm of neutrophils, but its roles-eventually extratelomeric effects-remain to be elucidated.